2023
DOI: 10.1007/s11357-023-00810-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in energy metabolism in peripheral mononuclear blood cells (PBMCs) and the brains of cognitively healthy seniors

Abstract: Mitochondrial dysfunction is a hallmark of cellular senescence and many age-related neurodegenerative diseases. We therefore investigated the relationship between mitochondrial function in peripheral blood cells and cerebral energy metabolites in young and older sex-matched, physically and mentally healthy volunteers. Cross-sectional observational study involving 65 young (26.0 ± 0.49 years) and 65 older (71.7 ± 0.71 years) women and men recruited. Cognitive health was evaluated using established psychometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Other studies have examined changes in mitochondrial respiration with age, although the older adults used were much older than the older group of parents in our study. One study found a decrease in ATP and ETC Complex IV activity in the PBMCs of older adults which did not correlate with markers of energy metabolism in the brain ( Silaidos et al, 2023 ). While another study also found a decrease mitochondrial respiration in the monocytes of older adults, the study did find that the mitochondria of older adults showed better coupling efficiency ( Sriwichaiin et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined changes in mitochondrial respiration with age, although the older adults used were much older than the older group of parents in our study. One study found a decrease in ATP and ETC Complex IV activity in the PBMCs of older adults which did not correlate with markers of energy metabolism in the brain ( Silaidos et al, 2023 ). While another study also found a decrease mitochondrial respiration in the monocytes of older adults, the study did find that the mitochondria of older adults showed better coupling efficiency ( Sriwichaiin et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%